2012
DOI: 10.1161/hypertensionaha.112.191098
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Cell Adhesion and Communication by Enhancer of Zeste Homolog 2 in Human Endothelial Cells

Abstract: The histone methyltransferase enhancer of zeste homolog 2 (Ezh2) mediates trimethylation of lysine 27 in histone 3, which acts as a repressive epigenetic mark. Ezh2 is essential for maintaining pluripotency of stem cells, but information on its role in differentiated cells is sparse. Whole-genome mRNA expression arrays identified 964 genes that were regulated by >2-fold 72 hours after small interfering RNA-mediated silencing of Ezh2 in human umbilical vein endothelial cells. Among them, genes associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 45 publications
5
54
0
1
Order By: Relevance
“…20,21,27 Consistently, the mRNA levels of EZH2 were reduced in GDM-HUVECs in comparison with control healthyHUVECs ( Figure 3A). Interestingly, we noticed that the EZH2-β isoform was decreased in GDM-HUVECs, whereas Gestational diabetes mellitus (GDM) is associated with expressional changes in microRNA-101 (miR-101) that affect the survival and angiogenic capacities of human umbilical vein endothelial cells (HUVECs).…”
Section: Ezh2 Is Downregulated In Gdm-huvecssupporting
confidence: 66%
See 1 more Smart Citation
“…20,21,27 Consistently, the mRNA levels of EZH2 were reduced in GDM-HUVECs in comparison with control healthyHUVECs ( Figure 3A). Interestingly, we noticed that the EZH2-β isoform was decreased in GDM-HUVECs, whereas Gestational diabetes mellitus (GDM) is associated with expressional changes in microRNA-101 (miR-101) that affect the survival and angiogenic capacities of human umbilical vein endothelial cells (HUVECs).…”
Section: Ezh2 Is Downregulated In Gdm-huvecssupporting
confidence: 66%
“…A recent report indicated a proangiogenic role for EZH2 in HUVECs 20,25 and identified 946 genes upregulated ≥2-fold because of EZH2 knockdown, 27 in accordance with the EZH2 transcriptional repressive function. Importantly, many of these EZH2-targeted genes are implicated in endothelial dysfunction and cardiovascular disease, 27 which is in line with the hypothesis that a decrease in EZH2 may confer an increased cardiovascular risk profile in the offspring from pregnancies complicated by GDM. If validated in population studies allowing for the follow-up of the children to maturity, this could help scientists understand whether there is any association between what is sensed in HUVECs and the incidence of vascular diseases.…”
Section: Discussionmentioning
confidence: 62%
“…It catalyzes H3K27me3. Transcriptomic studies suggest a relatively high expression of the EZH2 in ECs [104], which regulates the expression of multiple angiogenic pathways [105, 106]. We showed that EZH2 was upregulated at the protein level in SSc ECs compared to normal ECs, accompanied with increased levels of H3K27me3 [107].…”
Section: Epigenetic Impact In Ssc Pathogenesismentioning
confidence: 99%
“…3a and c). As IL1B is a putative EZH2-regulated gene [28], we speculated that IL-1β and EZH2 would form a regulatory feedback loop in endothelial cells. The decrease of EZH2 in IL-1β-stimulated HUVEC could lead to decrease of H3K27me3 at IL1B promoter and hence to an increase in IL1B/IL-1β expression.…”
Section: Positive Feedback Response Of Il1b Is Not Mediated By Ezh2 Amentioning
confidence: 99%
“…We hypothesized that histone methylation by Polycomb family members epigenetically regulates SM22α expression in endothelial cells. EZH2 modulates endothelial gene expression and is important for endothelial function [28,29]. As SM22α is synergistically induced by IL-1β and TGFβ2 in endothelial cells, we investigated the influence of IL-1β and TGFβ2 on the expression of EZH2 and the downstream role of EZH2 and H3K27me3 in mediating the effects of IL-1β and TGFβ2 and in the regulation of TAGLN/ SM22α expression in endothelial cells.…”
Section: Introductionmentioning
confidence: 99%